2017
DOI: 10.1007/s10798-017-9416-1
|View full text |Cite
|
Sign up to set email alerts
|

How school context and personal factors relate to teachers’ attitudes toward teaching integrated STEM

Abstract: Integrated STEM (Science, Technology, Engineering and Mathematics) education is an emerging approach to improve students' achievement and interest in STEM disciplines. However, the implementation of integrated STEM education depends strongly on teachers' competence, which entails, among others, teachers' attitudes. Nonetheless, not much is known about the factors that influence teachers' attitudes toward teaching integrated STEM. Therefore this paper uses a survey method to get insight into the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 69 publications
3
68
1
1
Order By: Relevance
“…In this research, "attitude" indicates whether the science teacher agrees or disagrees with the implementation of STEM (in students' classroom learning), the teachers' sense of curiosity towards STEM, and the teachers' thinking and feelings about STEM. Within the field of integrated STEM education, research on teachers' attitudes, especially as related to personal factors and personal points of view, is relatively scarce [22]. Therefore, accessing teachers' attitude regarding STEM education is significant in this current research.…”
Section: The Domain Of Attitude Knowledge and Application Of Stemmentioning
confidence: 99%
“…In this research, "attitude" indicates whether the science teacher agrees or disagrees with the implementation of STEM (in students' classroom learning), the teachers' sense of curiosity towards STEM, and the teachers' thinking and feelings about STEM. Within the field of integrated STEM education, research on teachers' attitudes, especially as related to personal factors and personal points of view, is relatively scarce [22]. Therefore, accessing teachers' attitude regarding STEM education is significant in this current research.…”
Section: The Domain Of Attitude Knowledge and Application Of Stemmentioning
confidence: 99%
“…The nature of the teaching subject constructs teaching assignments so teaching experiences in specific STEM domains are a predictive factor for differences in teachers' perceptions of STEM education [50]. For example, researchers [17] found that teachers who have experience in mathematics had a lower attitude toward teaching integrated STEM than other subjects. In our study, teaching subjects are hypothesized as demographic data to categorized teachers.…”
Section: Teaching Subjectsmentioning
confidence: 99%
“…Teachers play important roles in implementing STEM education successfully [15]. However, teaching practices are strongly affected by teachers' perceptions [15][16][17]. Thus, measuring teachers' perceptions of STEM education is evitable to sustain STEM deployment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, teachers' attitudes to and enactment of prescribed curricula are impacted by school context, such as leadership, scheduling, and concurrent reform initiatives. Thibaut et al have proved that school context is the most strongly related to teachers' attitudes toward teaching integrated STEM [43]. The implementation of integrated STEM education in K-12 requires effective and efficient instructional practice, too [44].…”
Section: Enactment Of Integrated Stem Educationmentioning
confidence: 99%